The Relationship Between Level Of Knowledge About (SADARI) Action As An Effort Forearly Detection Of Breast Cancer In Class X Students Of SMA Santo Thomas 1 Medan 2024 - Mardiati Barus; Jagentar P. Pane; Mentalitas Ndruru (Universitas Muhammadiyah Manado, 2024)
Knowledge is one of the factors that determine a person decision to take disease prevention measures. Knowledge may encourage the desire or motivation to carry out one of them breast self-examination (SADARI). It is an attempt to identify breast cancer at an earlier point. The knowledge of a person is useful for doing SADARI in a more regular and thorough way to detect breast cancer. This study aims to determine the relationship between the level of knowledge and the action of SADARI as an early detection of breast cancer.This study is cross-sectional, with an accidental sampling method of 67 respondents of class X female students. The instrument in this study used a questionnaire sheet. The results of the study obtain slightly more good knowledge as many as 34 respondents (50.7%), and more conscious actions are taken by 35 respondents (52.2%). The statistical test used chi square test p-value = ,000 where p <0.05 means that there is a relationship between the level of knowledge and the act of awareness as early detection of breast cancer. Researchers hope that respondents will conduct regular breast self-examination (SADARI) to prevent breast cancer.